Critical realism and political imaginaries in the poetry of Kusfitria Marstyasih - Setia Naka Andrian; Turahmat Turahmat (EduLite: Journal of English Education, Literature and Culture, 2026)
This study investigates how poetic realism and political imaginaries are constructed in 38, a poetry collection by Kusfitria Marstyasih. The objective is to examine how the poems articulate socio-political critique within the post-Reformasi Indonesian context. Using a qualitative textual analysis informed by the sociology of literature and the aesthetics of resistance, the study analysed selected poems to identify patterns of representation, tone, and thematic focus. The findings suggest that Marstyasih employs subtle realism through concise, ironic, and contemplative expression to critique power relations, human rights violations, and emotionally detached bureaucratic practices. Rather than presenting overt grand narratives, the poems operate as counter-discourses that quietly challenge dominant state ideology while foregrounding experiences of marginalization, denial, and symbolic death .The study concludes that 38 positions poetry as both aesthetic expression and civic engagement. The collection demonstrates how contemporary Indonesian poetry can function as a reflective space for cultural resistance and socio-political critique.